Haemoglobin structure and stability - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Myoglobin vs. haemoglobin, T-state and R-state of haemoglobin, Haemoglobin affinity for O2, The Bohr effect, Two models for O2 binding affinity
Reviewed at 2022/11/27